Factors Influencing the Rheological Properties of MRSP Based on the Orthogonal Experimental Design and the Impact Energy Test. (22nd September 2019) - Liu, Bing; Du, Chengbin; Fu, Yankai
Abstract : In the preparation process of magnetorheological silly putty (MRSP), the influence factors of the relative shear thickening effect (RSE) and relative magnetorheological effect (RME) were studied by orthogonal experiments as well as range and variance analyses. The influence degree of each factor was also evaluated. The results showed that the viscosity of polydimethylsiloxane (PDMS) and the mass fraction of carbonyl iron powder (CIP) had a significant influence on the RSE and RME, respectively. With an increasing PDMS viscosity, the RSE of the silicon-boron copolymer matrix first increased and then decreased, while the RME of MRSP decreased gradually. In addition, the shear thickening mechanism of MRSP was explored by the molecular chain motion. Finally, the impact energy with different samples was tested, and it is demonstrated that with the increasing cross section, the impact energy of the sample increases gradually, but the rate of increase becomes smaller.